1996
DOI: 10.1182/blood.v88.11.4390.4390
|View full text |Cite
|
Sign up to set email alerts
|

Two-way cell traffic between mother and fetus: biologic and clinical implications

Abstract: The bilateral trafficking of nucleated cells between the fetus and the mother was studied using polymerase chain reaction (PCR)-based systems sensitive enough to detect 1 target cell in 100,000 background cells. Sixty-six mother-baby pairs were recruited; maternal and cord blood samples were collected at delivery for DNA extraction. Cell trafficking was studied in informative cases using PCR-genotyping of polymorphic regions in the beta-globin cluster, the glutathione S-transferase M1 locus and the angiotensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 0 publications
3
71
2
Order By: Relevance
“…A number of publications have demonstrated that a regular transfer of maternal cells to the fetus takes place during all stages of the pregnancy (Petit et al ., 1995; Lo et al ., 1996), especially under pathologic conditions (Brune et al ., 2002b). In the immunocompetent fetus, this initiates no immune reaction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications have demonstrated that a regular transfer of maternal cells to the fetus takes place during all stages of the pregnancy (Petit et al ., 1995; Lo et al ., 1996), especially under pathologic conditions (Brune et al ., 2002b). In the immunocompetent fetus, this initiates no immune reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Using a FISH assay with X‐ and Y‐chromosome specific probes Hall et al [1995] detected maternal cells in 10 of 49 male umbilical cord blood specimens. Using a more sensitive assay for β globin polymorphisms, Lo et al [1996] found evidence of maternal cells in 16 of 38 cord blood samples. Antenatal transfer of maternal cells into the fetus occurs as early as 13 weeks of gestation [Lo et al, 1998a].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in alloimmunized pregnant women, there is a significant risk of boosting the maternal immune response to fetal RBC antigens. It is now established that during pregnancy there is two‐way trafficking of cells between the maternal and fetal circulation 4 . Therefore, fetal cells may be obtained from maternal peripheral blood for genetic analysis without endangering the fetus.…”
mentioning
confidence: 99%